Effect of wearing compression stockings on recovery after mild exercise-induced muscle damage - Bieuzen, F.; Brisswalter, J.; Easthope, C.; Vercruyssen, F.; Bernard, T.; Hausswirth, C. (International Journal of Sports Physiology and Performance, 2014)
Background: Compression garments are increasingly popular in long-distance running events where they are used to limit cumulative fatigue and symptoms associated with mild exercise-induced muscle damage (EIMD). However, the effective benefits remain unclear. Objective: This study examined the effect of wearing compression stockings (CS) on EIMD indicators. Compression was applied during or after simulated trail races performed at competition pace in experienced off-road runners. Methods: Eleven highly trained male runners participated in 3 simulated trail races (15.6 km: uphill section 6.6 km, average gradient 13%, and downhill section 9.0 km, average gradient -9%) in a randomized crossover trial. The effect of wearing CS while running or during recovery was tested and compared with a control condition (ie, run and recovery without CS; non- CS). Indicators of muscle function, muscle damage (creatine kinase; CK), inflammation (interleukin-6; IL-6), and perceived muscle soreness were recorded at baseline (1 h before warm-up) and 1, 24, and 48 h after the run. Results: Perceived muscle soreness was likely to be lower when participants wore CS during trail running compared with the control condition (1 h postrun, 82% chance; 24 h postrun, 80% chance). A likely or possibly beneficial effect of wearing CS during running was also found for isometric peak torque at 1 h postrun (70% chance) and 24 h postrun (60% chance) and throughout the recovery period on countermovement jump, compared with non-CS. Possible, trivial, or unclear differences were observed for CK and IL-6 between all conditions. Conclusion: Wearing CS during simulated trail races mainly affects perceived leg soreness and muscle function. These benefits are visible very shortly after the start of the recovery period.